2000
DOI: 10.1149/1.1394102
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Partial Fluorination of Organic Compounds XL. Solvent Effects on Anodic Fluorination of Heterocyclic Sulfides

Abstract: Solvent effects on electrolytic partial fluorination of ␣-(2-benzoxazolylthio)-, ␣-(2-benzothiazolylthio)-, and ␣-(2-pyrimidylthio)acetates were investigated systematically using acetontrile (MeCN) and 1,2-dimethoxyethane (DME) containing Et 4 NFиnHF (n ϭ 3, 4) as a supporting electrolyte and a fluoride ion source. MeCN was not suitable for the fluorination of these heterocyclic sulfides since formation of nonconductive polymers on the anode took place to result in low yields or no fluorination of fluorinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…In a solution such as DME, Et 4 NFÁ4HF may dissociate to Et 4 N + , F(HF)n À (n = 1-3), and HF [30][31][32][33]. Moreover, it was also found that DME was oxidized simultaneously during the electrolysis of substrates, which can suppress overoxidation of both the substrates and products, particularly at a later stage of the electrolysis [27].…”
Section: Solvent Effect On the Efficiency Of Selective Anodic Fluorinmentioning
confidence: 99%
See 1 more Smart Citation
“…In a solution such as DME, Et 4 NFÁ4HF may dissociate to Et 4 N + , F(HF)n À (n = 1-3), and HF [30][31][32][33]. Moreover, it was also found that DME was oxidized simultaneously during the electrolysis of substrates, which can suppress overoxidation of both the substrates and products, particularly at a later stage of the electrolysis [27].…”
Section: Solvent Effect On the Efficiency Of Selective Anodic Fluorinmentioning
confidence: 99%
“…On the other hand, we recently found that ethereal solvents like 1,2-dimethoxyethane (DME) were much more suitable than MeCN for the anodic fluorination of various heterocyclic sulfides as shown in Schemes 8 and 9 [27][28][29]. The use of MeCN results in extremely low yields or no formation of fluorinated products, while the use of DME markedly increases the yields.…”
Section: Solvent Effect On the Efficiency Of Selective Anodic Fluorinmentioning
confidence: 99%
“…The yield of 2a also decreased when the supporting electrolyte Et 3 N-5HF was used comparing with the case of Et 4 NF-4HF (Table 2, Run 10). It is known that dimethoxyethane (DME) is an excellent electrolytic solvent for anodic fluorination in some cases [20]. However, DME was not effective for the anodic fluorination of 1a regardless of supporting salt since DME is more easily oxidized than 1a.…”
Section: Anodic Fluorination Of O-methyl S-aralkyl Thiocarbonatesmentioning
confidence: 99%
“…This can be explained as follows. Since DME is more easily oxidized than CH 3 CN, DME was oxidized simultaneously during the electrolysis of the substrate 1b, which can suppress further oxidation of the product 2b, particularly at a later stage of the electrolysis [20]. However, a larger excess amount of electricity was required to obtain higher yield of 2b in DME due to the competitive anodic oxidation of DME (Runs 6 and 8).…”
Section: Anodic Fluorination Of O-methyl S-aralkyl Thiocarbonatesmentioning
confidence: 99%
“…We have systematically studied anodic monofluorination at the side chain of various heterocyclic compounds [7][8][9][10]. For example, selective anodic fluorination at the side chain of various heterocyclic compounds such as six-membered (2-pyridyl-and 4-pyrimidyl-), and five-membered (2-thiadiazolyl, 2-oxadiazolyl and 2-triazolyl) heterocycles was comparatively studied (Schemes 1 and 2) [11][12][13][14][15][16]. Thus, the active methylenethio group attached to various heterocyclic rings is selectively fluorinated to give the corresponding a-fluorinated products in moderate to good yields.…”
Section: Introductionmentioning
confidence: 99%